Pemetaan Store Design dan Visual Merchandising Distro di Kota Bandung - Jurry Hatammimi; Brhiyawan RH Cendekia (Forum Manajemen Indonesia (FMI), 2014)
One of the evidence of creative industry growth in fashion sector in the city of Bandung is the establishment of many distro or distribution outlet. There are 4 distro that has the highest sales level, i.e Ouval Research, Unkl347, Dloops, and Black Id. The four distro were trying to show differentiation in terms of store design and visual merchandising to make up the store uniqueness and influencing buying behavior. Beside there is no research about the mapping of distro in the city of Bandung yet, especially about their store design and visual merchandising, this study will also show the difference of the four distro even though they have some similarities. This study aims to determine the perceptual map of store design and visual merchandising which applied by each distro. By using Multi Dimensional Scaling, there are consumer assessment in making perceptual maps include shopping convenience, easy to find goods, shopping experience, signage, entrance, cash wraps, promotional aisle, windows, fitting room, traffic flow, alignment rack with the theme, the attractiveness of presentation techniques, and impulse purchase. The research shows Ouval Research superior in largely indicators namely shopping convenience, easy to find goods, shopping experience, signage, entrance, promotional aisle, windows, fitting room, the attractiveness of presentation techniques, and impulse purchase. Unkl347 win in two indicators namely cash wraps and alignment rack with the theme. Dloops only win in the traffic flow indicator. Black Id ranks fourth at all indicators. Keywords: Perceptual Map, Store Design, Visual Merchandising, Distribution Outlet